Dari Sungai Batang Kuantan ke FYP Dunia : Viralitas Pacu Jalur sebagai Diplomasi Budaya Digital Indonesia Kontemporer - Muhammad Tamrin; Rizqi Muhammad; Deni Dwi Pradana Hermansyah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Pacu Jalur is a traditional longboat race of the Malay community in Kuantan Singingi, Riau, which has served as a symbol of local cultural identity since the 17th century. In the last three years, this tradition has gone viral on TikTok, reaching millions of international viewers through hashtags such as #pacujalur and #indonesianboatracing. This study aims to analyze the role of Pacu Jalur’s virality as an instrument of Indonesia’s cultural diplomacy in the digital era. The method used is literature study with a thematic analysis approach, combining theories of soft power, digital cultural diplomacy, and cultural identity. The results show that Pacu Jalur’s virality expands cultural exposure to global audiences and strengthens local identity, while simultaneously highlighting the collective values of solidarity, teamwork, and aesthetic traditions embedded in the longboat race. At the same time, this phenomenon raises potential risks of cultural distortion due to commercialization, over-simplification of meaning, and the dominance of digital content logic that prioritizes visual appeal and entertainment value over historical and spiritual dimensions. These findings underscore the dual nature of viral cultural content: as both an opportunity for cultural diplomacy and a challenge for authenticity preservation. Therefore, this research highlights the importance of digital literacy, strategic collaboration between cultural stakeholders, and adaptive policy frameworks to ensure that the viral presence of Pacu Jalur on global digital platforms reflects authentic cultural values and serves as a sustainable instrument of Indonesia’s soft power in the contemporary international arena.